The Asset Allocation of Emerging Market Mutual Funds - Disyatat, Piti (International Monetary Fund, 2001)
Benchmark following and portfolio rebalancing effects have often been cited when trying to explain international financial contagion phenomena. Using a dataset containing the country allocation of individual dedicated emerging market equity funds, we assess the relevance of mean-variance optimization and benchmark following, finding strong evidence for both. We also present a framework to systematically extract useful information about market expectations from funds'' holdings